Cover Picture: Confined Self‐Assembly in Two‐Dimensional Interlayer Space: Monolayered Mesoporous Carbon Nanosheets with In‐Plane Orderly Arranged Mesopores and a Highly Graphitized Framework (Angew. Chem. Int. Ed. 11/2018). Issue 11 (19th February 2018) - Wang, Jie; Xu, Yunling; Ding, Bing; Chang, Zhi; Zhang, Xiaogang; Yamauchi, Yusuke; Wu, Kevin C.‐W.
Abstract : Mesoporous carbon nanosheets are prepared through assembly of a carbon precursor and a block copolymer in the confined interlayer space of montmorillonite. X. Zhang, K. C.‐W. Wu, and co‐workers show in their Communication on page 2894 ff. that ordered mesopores exposed on the carbon nanosheet realize efficient diffusion of guest molecules from outside. The confined environment favors the formation of highly graphitic carbon, which can achieve fast electron transportation.